The Influence of Sufism in Indonesian Islamic Spirituality: A Contemporary Reinterpretation - Wijaya Wijaya; Haruka Sato; Daiki Nishida (Yayasan Adra Karima Hubbi, 2025)
This study explores the enduring and evolving influence of Sufism on Indonesian Islamic spirituality, examining its contemporary reinterpretation amidst modern challenges. Indonesian Islam has historically embraced mystical traditions, fostering a unique spiritual landscape distinct from more legalistic or fundamentalist expressions. Understanding this dynamic is crucial for appreciating the breadth of Islamic practice in the archipelago. The research aims to analyze how Sufi practices and philosophies are adapted and re-articulated by contemporary Indonesian Muslims, identifying the motivations behind this reinterpretation and its impact on individual and communal spirituality. Employing a qualitative research design, this study utilizes in-depth interviews with 25 Sufi practitioners, scholars, and community leaders across Java and Sumatra. Observational data from Sufi tariqa gatherings and contemporary spiritual forums further enriched the findings. Thematic analysis was used to identify recurring patterns and interpretations. Results indicate a significant re-engagement with Sufism, driven by a search for inner peace, spiritual authenticity, and a moderate alternative to rigid interpretations of Islam. The study found that Sufism continues to be a vital source of spiritual resilience and ethical guidance. In conclusion, Sufism remains a powerful force in Indonesian Islamic spirituality, offering a dynamic and adaptable framework for contemporary religious life. Its reinterpretation underscores its enduring relevance in cultivating a compassionate and tolerant Muslim identity.